2014
DOI: 10.5644/ama2006-124.96
|View full text |Cite
|
Sign up to set email alerts
|

Immune responses following McKenzie lumbar spine exercise in individuals with acute low back pain: A preliminary study

Abstract: Objective. This study explores the immune responses following 4 weeks of McKenzie lumbar spine exercise in individuals with acute low back pain (ALBP). Patients and methods. Fifteen patients with ALBP and 15 healthy individuals volunteered in this study. Ten ml of peripheral blood were obtained from each patient before and after exercise sessions, and from healthy individuals at the beginning of the study.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
6
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 50 publications
2
6
0
Order By: Relevance
“… Al-Obaidi & Mahmoud (2014) recently reported on a study with characteristics similar to ours, which found increased production of pro-inflammatory cytokine TNF- α after treatment, but no change in IL-6 production. The author justified this result by stating that overexpression of TNF- α and other pro-inflammatory cytokines occurs in many studies of low-back pathologies ( Takahashi et al, 1996 ).…”
Section: Discussionsupporting
confidence: 74%
“… Al-Obaidi & Mahmoud (2014) recently reported on a study with characteristics similar to ours, which found increased production of pro-inflammatory cytokine TNF- α after treatment, but no change in IL-6 production. The author justified this result by stating that overexpression of TNF- α and other pro-inflammatory cytokines occurs in many studies of low-back pathologies ( Takahashi et al, 1996 ).…”
Section: Discussionsupporting
confidence: 74%
“…Our results with regard to inflammation indicate that, following TTEP, TNF-α levels had increased; when SSEP was used, IL-6 levels had increased by the end of our 20-session course of treatment. Al-Obaid et al, recently reported on a study with characteristics similar to ours, which found increased production of pro-inflammatory cytokine TNF-α after treatment, but no change in IL-6 production (Al-Obaidi & Mahmoud, 2014). The author justified this result by stating that overexpression of TNF-α and other pro-inflammatory cytokines occurs in many studies of lowback pathologies (Takahashi et al, 1996).…”
Section: Discussionsupporting
confidence: 63%
“…However, the mechanisms of the immune system’s action on LDH have been discussed in various studies, mainly focusing on cytokine and immunoglobulins ( Naylor et al, 1975 ; Miyamoto et al, 2000 ; Shamji et al, 2010 ). Regarding immune factors, previous studies ( Miyamoto et al, 2000 ; Shamji et al, 2010 ; Al-Obaidi and Mahmoud, 2014 ; Djuric et al, 2020 ) detected the presence of large amounts of IL-1β, IL-17, and IL-10 in the intervertebral discs of patients with LDH and investigated the mechanism of their action on LDH. The results showed a significant negative correlation between the concentrations of IL-1β and IL-17 and the condition of LDH ( Al-Obaidi and Mahmoud, 2014 ; Tan et al, 2022 ).…”
Section: Biological Mechanisms Of Exercise In the Treatment Of Ldhmentioning
confidence: 99%
“…Regarding immune factors, previous studies ( Miyamoto et al, 2000 ; Shamji et al, 2010 ; Al-Obaidi and Mahmoud, 2014 ; Djuric et al, 2020 ) detected the presence of large amounts of IL-1β, IL-17, and IL-10 in the intervertebral discs of patients with LDH and investigated the mechanism of their action on LDH. The results showed a significant negative correlation between the concentrations of IL-1β and IL-17 and the condition of LDH ( Al-Obaidi and Mahmoud, 2014 ; Tan et al, 2022 ). At the same time, IL-10, a critical immunosuppressive factor, had a significant positive correlation with the condition of LDH ( Uçeyler et al, 2007 ).…”
Section: Biological Mechanisms Of Exercise In the Treatment Of Ldhmentioning
confidence: 99%